The complete sentence model as a pedagogical intervention to enhance students’ critical thinking skills in social studies learning - Fina Nurul Arifah; M Asror (Privietlab, 2026)
This research was motivated by the low critical thinking skills of students in Social Studies (IPS) learning, which often remains textual and teacher-centered. This study aimed to (1) describe the implementation of the Complete Sentence learning model, (2) analyze students' critical thinking skills before and after the model's implementation, and (3) examine the significance of the difference in critical thinking skills between the class applying the Complete Sentence model and the class that did not. This study employed a quantitative approach with a quasi-experimental Non-Equivalent Control Group Design. The population consisted of all eighth-grade students at SMPN 2 Pangenan, with a sample of 60 students divided into an experimental group (Class VIII A, n=30) and a control group (Class VIII D, n=30). The research instruments included a critical thinking skills test (measuring C3 and C4 levels) and a model implementation questionnaire. The results showed that the model implementation was